2020
DOI: 10.1111/jorc.12351
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions of Turkish Cypriot patients receiving haemodialysis: A qualitative study

Abstract: Background Illness perceptions refer to cognitive appraisals that help patients understand and make sense of their condition. Although their importance in health behaviour and outcomes has been evidenced, less is known about cultural influences on mental representations of kidney failure amongst patients receiving haemodialysis in different settings. Objective To explore the illness perceptions of Turkish patients receiving haemodialysis in North Cyprus (Turkish Cypriots). Design A qualitative study involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This will have an impact on participants in living their lives. Research conducted by Keskindag et al (7) found that patients undergoing hemodialysis experienced psychological disturbances.…”
Section: Theme Iii: Psychological Burden During Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This will have an impact on participants in living their lives. Research conducted by Keskindag et al (7) found that patients undergoing hemodialysis experienced psychological disturbances.…”
Section: Theme Iii: Psychological Burden During Treatmentmentioning
confidence: 99%
“…These two things have a negative impact on the quality of life of CRF patients undergoing hemodialysis. Research conducted Keskindag et al (7) found that qualitatively, patients undergoing hemodialysis therapy experienced physical, psychological and emotional complaints. Quality of Life is also influenced by social support and age of the patient (8) .…”
Section: Introductionmentioning
confidence: 99%